MOLECULAR-GENETIC FEATURES WOMEN WITH POLYCYSTIC OVARY SYNDROME (PCOS) - Анжелика Юрьевна Беглова; Светлана Ивановна Елгина; Наталья Владимировна Артымук; Людмила Александровна Гордеева (The Publishing House Medicine and Enlightenment, 2019)
Aim - the study of the polymorphism of CYP11A1, CYP17A1, CYP19A1 genes in women with polycystic ovary syndrome (PCOS) of reproductive age in comparison with women without PCOS. Materials and methods. The study included 188 women of reproductive age. Group I consisted of 94 women with PCOS; Group II - 94 women without PCOS. All patients were subjected to molecular genetic analysis of SNP polymorphisms of the VNTR genes of the pentanucleotide ((tttta)n polymorphism at position -528 of the promoter region of the CYP11A and CYP17A1 gene (-34T>C(MspA1), rs743572) and CYP19A1 (c.-39+15658 C>T, C40824T, rs2470152) using the test system OOO SibNK. The amplification reaction was performed using the Real-time PCR detection system - CFX96, followed by statistical data processing. Results. The frequency distribution of genotypes of CYP11A1 (tttta)n, CYP17A1 rs743572 and CYP19A1 rs2470152 genes in groups of women with PCOS and in healthy women was not statistically significantly (p > 0.05). However, for CYP11A1 (tttta)n polymorphism, there was a tendency for accumulation of alleles with a large number (tttta) of n-repeats in women with PCOS than in healthy women. Typical were VNTR genotypes with 6/6, 6/8 and 8/8 pentanucleotide repeaters. Conclusion. Apparently, in the women we surveyed, the genetic factor did not play a key role in the development of PCOS. Our study may be useful for further meta-analyzes that may allow us to reveal the idea of the pathogenesis of the disease.